Multiple uses of dexmedetomidine in small animals: a mini review - Di Franco, Chiara; Evangelista, Flavia; Briganti, Angela (Frontiers in Veterinary Science, 2023)
Dexmedetomidine is an alpha-2 adrenergic agonist, which use had an exponential increase in human and veterinary medicine in the last ten years. The aim of this mini review is to summarize the various uses of dexmedetomidine underlining its new applications and capabilities in the small animals’ clinical activity. While this drug was born as sedative in veterinary medicine, some studies demonstrated to be effective as an analgesic both in single administration and in continuous infusion. Recent studies have also shown the role of dexmedetomidine as an adjuvant during locoregional anaesthesia, increasing the duration of the sensitive block and consequently decreasing the demand for systemic analgesics. The various analgesic properties make dexmedetomidine an interesting drug for opioid-free analgesia. Some studies highlighted a potential neuroprotective, cardioprotective and vasculoprotective role of dexmedetomidine, thus conferring it a place in critical care medicine, such as trauma and septic patients. Dexmedetomidine has demonstrated to be a multitasking molecule and it is ready to face new challenges.